SPEECH GENDER STEREOTYPES IN CONFLICT DISCOURSE (American Journal of Interdisciplinary Research and Development, 2025)
This article examines the impact of speech gender stereotypes on conflict discourse. Gender stereotypes shape expectations regarding communication styles, often influencing the perception and participation of individuals in conflict situations. By analyzing speech patterns, power dynamics, and cultural narratives, this study demonstrates how these stereotypes perpetuate inequities in conflict engagement and resolution. The findings highlight the need for awareness and training to mitigate the effects of these biases, fostering a more inclusive approach to communication in conflict scenarios.